Analysis of Improving Science Process Skills Through the Development of Guided Inquiry-Based E-Modules: A Literature Review - Melani Aulia Khatami; Salwa Nur Sapiatun Nakjah (Indonesian Publication Center, 2026)
The development of technology in education encourages the use of innovative digital learning materials to improve the quality of science learning. This study aims to analyze various research findings regarding the use of guided inquiry-based e-modules in science learning and their impact on students’ science process skills. The method used in this study is a literature review by analyzing several scientific articles relevant to the research topic. These articles were examined to identify research objectives, research methods, and key findings related to the use of e-modules and guided inquiry learning models in science education. The results show that the use of guided inquiry-based e-modules has significant potential to improve student engagement, conceptual understanding, and science process skills. In addition, e-modules present learning materials in a more systematic, attractive, and interactive manner, helping students understand scientific concepts more effectively. Therefore, integrating guided inquiry-based e-modules can be an effective alternative learning strategy to improve the quality of science learning.